2013
DOI: 10.1108/apjba-02-2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Emotional labour and its outcomes: a study of a Philippine call centre

Abstract: Purpose -The purpose of this paper is to examine whether Western human resource (HR) theory is applicable to a call centre located in the Philippines. A call centre, due to the amount of emotional labour involved in this type of work, is an ideal environment to study stress related Western HR model where stress eventually leads to turnover. Turnover is a major concern in the call centre industry. Design/methodology/approach -The authors tested a model linking work stress to job satisfaction, organizational com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…These so-called 'identity demands' are unique to the offshore context (Das, 2012, p. 369;Nadeem, 2011;Thite & Russell, 2010). Moreover, to the extent that the heightened level of hostility that destination workers experience also heightens the difficulty of maintaining a positive interaction, emotional labor requirements in the offshore context will be at a level of intensity that differs significantly from the inshore context (Ruppel et al, 2013;Thite & Russell, 2010).…”
Section: The Offshore Contextmentioning
confidence: 92%
See 1 more Smart Citation
“…These so-called 'identity demands' are unique to the offshore context (Das, 2012, p. 369;Nadeem, 2011;Thite & Russell, 2010). Moreover, to the extent that the heightened level of hostility that destination workers experience also heightens the difficulty of maintaining a positive interaction, emotional labor requirements in the offshore context will be at a level of intensity that differs significantly from the inshore context (Ruppel et al, 2013;Thite & Russell, 2010).…”
Section: The Offshore Contextmentioning
confidence: 92%
“…This is because source country customers often become angered and frustrated when, due to language and/or cultural differences, they have trouble understanding, and/or being understood by, the destination employees trying to help them (Sizoo, KĂĽpper, & Agrusa, 2011). Customers can become particularly hostile if they believe that the workers they are interacting with have 'stolen' source country jobs (Ruppel, Sims, & Zeidler, 2013;Thite & Russell, 2010). Racist remarks are not uncommon (Nadeem, 2011;Thite & Russell, 2010).…”
Section: The Offshore Contextmentioning
confidence: 96%
“…The results of the study in the Philippines showed, that the employees of call-center has emotional stress at work, that affects job dissatisfaction, a decrease in commitment to the organization, and an increased desire to change this work (Ruppel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There is a high turnover rates in the Philippine call center with sources as physical and psychological impact of work schedule, lack of social support and social isolation [6]. Accordingly, turnover is a serious and increasing problem in call center and turnover rates in call center is extremely high which suggests call center as an ideal environment in which to study stress and burnout [7]. A study indicated that the factors of burnout like emotional exhaustion, depersonalization, and reduced personal accomplishment increased turnover intentions [8].…”
Section: Introductionmentioning
confidence: 99%
“…If this is the case, those who may be experiencing the exhaustion part of the work are those who stayed in the company for a long time because they are the one's handling the escalation part of handling difficult customers because as supervisor they are more able to address this kind of issue. [7] Table 2 presents the level of cynicism for the call center agents with an alarming 59.7% of the call center agents with high cynicism. More than half of the call center agents reported to be feeling indifferent or having a distant attitude toward their work.…”
mentioning
confidence: 99%